Strategi Pengajaran Tahsin Dan Tahfidz Menggunakan Metode Muri-Q Di Markaz Tahfidz Nusantara Gemolong - Fauzan Ahmad Al Anshori; Nanang Pujiyanto; Sri Handayani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to identify the strategy of the Muri-Q method in improving the Qur’anic recitation (tahsin) and memorization (tahfidz) skills of students at Markaz Tahfidz Nusantara Gemolong Sragen. The background of this study arises from the need for a structured method that integrates proper Qur’anic reading and systematic memorization reinforcement. The Muri-Q method is a learning approach based on thematic tajwid, progressive repetition, and structured revision (muroja’ah). This research uses a qualitative descriptive approach with data collected through observation, in-depth interviews, and documentation. The research subjects consist of thirty students, two teachers, and one manager of the tahfidz house. The findings show that the Muri-Q method positively impacts students’ recitation quality according to tajwid rules and accelerates memorization achievement. Furthermore, the method enhances students’ learning motivation and discipline. Supporting factors include intensive mentoring, personalized teaching, and a conducive learning concept. However, challenges remain due to the limited number of teachers who fully understand the Muri-Q method. These findings suggest that the method can be adapted more widely in similar institutions, provided that sufficient teacher training is ensured.